2020
DOI: 10.14715/cmb/2020.66.6.21
|View full text |Cite
|
Sign up to set email alerts
|

MiR-381-3p/RAB2A axis activates cell proliferation and inhibits cell apoptosis in bladder cancer

Abstract: Acting as a really common cancer in the world, bladder cancer has taken many people's life away. MiRNAs and mRNA have been reported can regulate the expression of cancers. In this study, the role of RAB2A and miR-381-3p was fully studied in bladder cancer. qRT-PCR assay probe the expression of RAB2A and miR-381-3p in bladder cancer cells. Meanwhile, colony formation assay, EdU assay, flow cytometry analysis, JC-1 assay and western blot assay were implemented to detect the progression of bladder cancer cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A research of bladder cancer in vitro showed miR-381-3p inhibits the progression of bladder cancer cells by binding to RAB2A (Ras-Related Protein Rab-2A). Another experiment also proved that miR-381-3p blocks the dual regulatory role of CCNA2 (Cyclin-A2) in modulating CDK6 and MET-mediated cell-cycle pathway and EMT progression in bladder cancer [ 30 , 31 ]. Identical to miR-381-3p, miR-451a acts as anti-cancer factor in various cancer and inhibits the proliferation, migration and invasion of cancer cells [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A research of bladder cancer in vitro showed miR-381-3p inhibits the progression of bladder cancer cells by binding to RAB2A (Ras-Related Protein Rab-2A). Another experiment also proved that miR-381-3p blocks the dual regulatory role of CCNA2 (Cyclin-A2) in modulating CDK6 and MET-mediated cell-cycle pathway and EMT progression in bladder cancer [ 30 , 31 ]. Identical to miR-381-3p, miR-451a acts as anti-cancer factor in various cancer and inhibits the proliferation, migration and invasion of cancer cells [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Rab proteins regulate signal transduction, cell development, and differentiation. Previous research has shown that abnormal Rab expression is strongly linked to genetic problems, in ammation, neurological disorders 18 , diabetes 19 , and a variety of cancers 20 , such as bladder cancer 21 , breast cancer 5,22,23 , oral cancer 24 , and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-522-3p is an oncogene in glioblastoma by targeting SFRP2 through the Wnt/β-catenin pathway [ 42 ]. The miR-381-3p/RAB2A axis induces cell proliferation and inhibits cell apoptosis in bladder cancer [ 43 ]. MiR-381-3p targeted and suppressed the NASP gene, and reduced viability, migration, invasion and EMT in HNSCC cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%